2017
DOI: 10.1177/1053825917696832
|View full text |Cite
|
Sign up to set email alerts
|

Applying Kolb’s Model to a Nontraditional Preservice Teaching Practicum

Abstract: This article reports on the initial findings of an ongoing study that will see six preservice teachers placed in a nontraditional practicum placement as part of their bachelor of education program. Reported here is the examination of emergent professionalism of the initial two preservice teachers during their nontraditional practicum placement on a housing construction site. Emergent professionalism is enacted when teachers shift their concerns from self to other, as described by Fuller. The findings are then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…This finding suggested that the participants began to demonstrate emergent professionalism as seen from their focus on students' learning rather than on concerns about their teaching performance associated with the evaluative nature of the Micro Teaching class. This finding was in line with a study by Burns and Danyluk (2017) involving six pre-service language teachers. They found that through a teaching practicum experience, their participants realized the elements of learning most valued by their students, such as whether the lesson was engaging, relevant, or authentic (Burns & Danyluk, 2017).…”
Section: Sub-theme 12 Realizing the Need To Adjust Instruction To Sui...supporting
confidence: 92%
See 2 more Smart Citations
“…This finding suggested that the participants began to demonstrate emergent professionalism as seen from their focus on students' learning rather than on concerns about their teaching performance associated with the evaluative nature of the Micro Teaching class. This finding was in line with a study by Burns and Danyluk (2017) involving six pre-service language teachers. They found that through a teaching practicum experience, their participants realized the elements of learning most valued by their students, such as whether the lesson was engaging, relevant, or authentic (Burns & Danyluk, 2017).…”
Section: Sub-theme 12 Realizing the Need To Adjust Instruction To Sui...supporting
confidence: 92%
“…They teach based on specific methods they have learned in the majors strictly with little regard for their students' needs or proficiency level. The evaluative nature of teaching practice classes, where both teacher mentors and their teachers assess pre-service teachers' teaching, may make them focus on their performance (Burns & Danyluk, 2017). Kuswandono (2017) argued that such an attitude of self-orientation during school-based practicum may lead pre-service teachers to neglect the importance of good social interactions, including with students, which may be necessary for their professional learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Community engagement is central to the process (Deringer, 2017), where learners themselves are central to the context (cf. Burns, & Danyluk, 2017). Blair (2016) identifies that the nature of knowledge construction is a social process (highlighting the works of Dewey, Piaget, and Vygotsky).…”
Section: Research Question 1: What Constitutes a Concrete Experience?mentioning
confidence: 99%
“…By understanding one's learning style, one will be able to develop the skills that help one learns in a variety of ways to achieve full potential. Further, this understanding will assist teach-ers to enable them to match their teaching styles, methodologies and course organization with learners' learning styles to help learners improve their learning (Burns and Danyluk, 2017;Cornett, 1983;Sato & Laughlin, 2018).…”
Section: Introductionmentioning
confidence: 99%